Extension of the Modified Julia Olefination on Carboxylic Acid Derivatives: Scope and Applications - Gueyrard, David (Synlett, 2018)
This account relates our work in the field of modified Julia olefination to extend this very useful olefination method to carboxylic acid derivatives. Since our preliminary results on lactones in 2005, the reaction has been extended to a large range of derivatives (lactams, imides and anhydrides) through an intra- or intermolecular process leading to a great variety of structures (enol ethers, enamides and exo enol esters). This article will also focus on the application of this methodology for the preparation of biologically interesting compounds and/or total syntheses of natural products such as C-disaccharide, bistramide A, jaspine B and maculalactone B.1 Introduction2 Modified Julia Olefination on Lactones2.1 Methylene Enol Ether Synthesis2.2 Substituted Enol Ether Synthesis2.3 Monofluorinated Enol Ether Synthesis2.4 Difluorinated Enol Ether Synthesis3 Applications3.1 Spiroketal Synthesis3.2 Spirocompound Synthesis3.3 Pseudodisaccharide Synthesis3.4 Total Synthesis of Jaspine B4 Modified Julia Olefination on Other Carboxylic Acid Derivatives4.1 Lactam Olefination and Spiroaminal Synthesis4.2 Bicyclic Enamide Synthesis by Intramolecular Modified Julia Olefination on Imides4.3 Modified Julia Olefination on Anhydrides5 Conclusion
Keywords: modified Julia olefination; alkenes; total synthesis; enol ethers; spiroketals